Awareness of diabetes and lifestyle practices among patients attending tertiary care hospitals in Patiala, Punjab - Kaleka, Amritpal Singh; Kaur, Manpreet; Kaur, Manmeet Pal (International Journal of Research in Medical Sciences, 2026)
Background: India often referred to as the “diabetes capital of the world,” faces a growing diabetes burden driven by sedentary lifestyles, unhealthy dietary habits, and limited awareness. Punjab, in particular, has shown a steep rise in diabetes prevalence. The present study has been carried with the aim to assess awareness and lifestyle behaviors among diabetic patients in Patiala, Punjab for identifying existing gaps for effective management and education. Methods: A cross-sectional survey was conducted among 100 diabetic patients attending outpatient departments of three hospitals in Patiala. The socio-demographic information, diabetes awareness (blood glucose monitoring, HbA1c testing, eye screening), and lifestyle practices (diet, exercise and substance use) have been documented. Results: The majority of participants had a balanced gender ratio, were between the ages of 60 and 70, and had a significant percentage of positive family histories of diabetes. Only over half of the participants knew their target glucose levels, despite the fact that regular blood sugar monitoring (92%) and HbA1c testing (86%) were routine. There was a high rate of medication adherence, but with little professional nutrition advice or eye examination. Though alcohol consumption and smoking were observed uncommon, but physical inactivity became a major concern. Conclusions: In conclusion, there are still knowledge gaps in glycemic objectives, preventative screenings, and physical exercise despite good treatment compliance and frequent monitoring. To improve long-term disease outcomes in Punjab, focused diabetes education and lifestyle modification programs are crucial.